Formant frequencies and vowel space area in Javanese and Sundanese English language learners - Perwitasari, Arum; Klamer, Marian; Schiller, Niels O. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Several studies have documented how first language (L1) vowel systems play an important role in the vowel production of a second language (L2). L2 learners of Western languages who exhibit a smaller L1 vowel system are predicted to struggle with producing L2 vowels. However, there remains a paucity of evidence on how the L1 vowel system of non-Western languages interferes with L2 vowel production In this case, the focus is specifically on Javanese and Sundanese, two of the most widely spoken Indonesian local languages. This present study investigated how the six Javanese vowels and the seven Sundanese vowels influence the production of ten English vowels. In this experiment, 40 speakers, Javanese, Sundanese, and 10 native English speakers, participated in the production task. Spectral dimensions, including first (F1) and second formant (F2) frequencies, were analysed acoustically. According to the Speech Learning Model, Javanese and Sundanese speakers should have trouble producing similar vowels such as (/I, ɛ, ʊ/) and should not exhibit greater L2 differences with new vowels such as (/i:, æ, ɑː, ɔ:, u:, ʌ, ɜ:/). Indeed, the results demonstrated that the Javanese speakers did have different F1 and F2 values with the English vowels (/i:, æ, ɑː, ɔ:, u:, ʌ, ɜ:/) and the Sundanese speakers produced different F1 and F2 values for vowels (/æ, ɑː, ɔ:/) when compared to the English native speakers. Interestingly, though vowels (/I, ʊ/) were considered to be similar vowels in the L1 vowel system, the Javanese and Sundanese speakers also showed differences in the formant structure. The vowel space area in the productions by Javanese and Sundanese speakers was slightly smaller than that of the native English speakers. The present study is expected to serve as a basis for future studies and provide the patterns of English vowels produced by Javanese and Sundanese learners of English.